Multicore Acceleration of Priority-Based Schedulers for Concurrency Bug Detection - Nagarakatte, Santosh; Burckhardt, Sebastian; Martin, Milo M. K.; Musuvathi, Madan (Programming Languages Design and Implementation, 2012)
Testing multithreaded programs is difficult as threads can interleave in a nondeterministic fashion. Untested interleavings can cause failures, but testing all interleavings is infeasible. Many interleaving exploration strategies for bug detection have been proposed, but their relative effectiveness and performance remains unclear as they often lack publicly available implementations and have not been evaluated using common benchmarks. We describe NeedlePoint, an open-source framework that allows selection and comparison of a wide range of interleaving exploration policies for bug detection proposed by prior work. Our experience with NeedlePoint indicates that priority-based probabilistic concurrency testing (the PCT algorithm) finds bugs quickly, but it runs only one thread at a time, which destroys parallelism by serializing executions. To address this problem we propose a parallel version of the PCT algorithm (PPCT).We show that the new algorithm outperforms the original by a factor of 5 when testing parallel programs on an eight-core machine. We formally prove that parallel PCT provides the same probabilistic coverage guarantees as PCT. Moreover, PPCT is the first algorithm that runs multiple threads while providing coverage guarantees.